Student's perspectives regarding e-service quality of My UTM portal - Leow, Yong Kean 1994- , author 612030; Siti Zaleha Omain supervisor 287888; Fakulti Pengurusan 538641 (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2018)
Project Paper (Sarjana Muda Pengurusan (Teknologi)) - Universiti Teknologi Malaysia, 2018